Strategi Pengembangan Sumber Daya Manusia Di Lembaga Pendidikan Islam Indonesia - Sholeh, Muh Ibnu (Indonesia Islamic Education Journal, 2023)
In the era of globalization and the industrial revolution 4.0, the strategy for developing human resources in Islamic educational institutions is becoming increasingly important. Islamic educational institutions need to prepare students and educational staff to face future challenges with adequate skills and abilities. Therefore, Islamic educational institutions need to develop an effective and sustainable human resource development strategy, by involving all relevant parties and with the support of adequate resources. This study used the library research method by conducting an analysis of literature studies related to human resource development strategies in Islamic educational institutions. Literature studies are obtained from various sources such as scientific journals, books, seminar papers, and other related publications related to the research topic. The results of this study indicate that various human resource development strategies that can be carried out by Islamic educational institutions include training and development, apprenticeship programs, scholarships and awards, mentorship programs, increasing human resource welfare, collaboration with other institutions, evaluating human resource performance, spiritual coaching, technology implementation, and innovation development. With the right human resource development strategy, Islamic education institutions can have quality human resources and be able to meet the needs of Islamic education